Comparison of The Effectiveness Between Preoperative Ibuprofen Verses Placebo On the Success of the Inferior Alveolar Nerve Block in Patients with Irreversible Pulpitis: Preoperative Ibuprofen Verses Placebo effect in Irreversible Pulpitis - Siddiqui, Tanveer Ahmed; Rehman, Amna; Rajput, Fozia; Tahir, Asad; Anwar Memon, Aosaf; ., Abdullah (Pakistan Journal of Health Sciences, 2023)
The inferior alveolar nerve block is the simplest often utilized injection procedure in dentistry, and numerous variations of the traditional nerve block have lately been reported. The dentist or surgeon must consider a variety of aspects before choosing the optimum approach, considering the treatment's effectiveness probability and potential problems. Objective: To compare the effectiveness of preoperative ibuprofen verses placebo in enhancing the success of inferior alveolar nerve block in patients with irreversibly inflamed pulp. Methods: This randomized control trial was performed for a period of 6 months. Data collection was done after taking approval from hospital ethical committee of Altamash Institute of Dental Medicine. 236 patients were included in this study. The participant was told to assess their level of discomfort after the endodontic treatment. Results: From 236 patients, the minimum age was found 18 years and maximum age was 45 years. Males were 123/236 (52.1%) while females were 113/236 (47.9%). Effectiveness of both materials was found in 74/236 (31.4%) patients. Effectiveness of materials was found significant in both groups (Ibuprofen, Placebo) having p-value 0.012. Conclusions: The effectiveness of materials was significant in both groups (Ibuprofen, Placebo). Effect modifier like age, duration of pain and gender has no significant association with effectiveness of materials.